Impact of maturation on junior elite AFL athletes movement proficiency and field based performance - Ball, N.; Riddington, S.; Ibbott, P.; Hunt, D. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Assessing junior athlete`s movement capabilities is important to enhance long term development, and is considered to discriminate between levels of pubescence and identify injury problems (Paszkewicz et al, 2013; Kiesel, et al, 2007). Little work has been done to assess the movement abilities of elite junior athletes and its relation to field based fitness tests, whilst also considering the impact of maturation on movement screen variables. Methods: 42 junior elite athletes (U16 n=22, U18 n=20) underwent anthropometric, movement screen and fitness testing (20m and 40 m sprint, running jump, CMJ, MSFT, Yo-Yo, 3km). The movement screen comprised of 6 actions (Lunge & return, jump & single leg hold, single-leg bridge, vertical CMJ, push-up, squat) and were judged on an ordinal scale (0=poor; 3=competent) by qualified strength coaches. Correlations were used to assess the relationships of movement screen and anthropometrics to fitness scores. Independent t-tests were used to compare fitness variables between groups (U16 vs U18) (P=0.05). Results: Age at Peak height velocity did not correlate with any fitness or movement screen variable. Height and leg length had moderate correlations with repeated shuttle and MST test (R=0.30-0.35), whereas leg length negatively correlated with the lunge & return and jump and single leg hold (R=-0.38>-0.44). The U18 group had superior results (p<0.05) to the U16 group in jump & single leg hold, all sprint tests, CMJ and Yo-Yo. Discussion: This study supports previous literature showing little relationship between movement screens and physical performance in mature age athletes (Parchmann and McBride, 2011). Maturation did not relate to movement screen performance, indicating that between 1-4 years post PHV no differences in movement proficiency exist. Thus observed differences in physical performance are likely due to increased training age and muscle strength that accompanies being further from the age at peak height velocity (Carvalho et al, 2012). The benefit of movement screens in terms of performance enhancement may lay in improving the ability to train opposed to manifest themselves in direct relation to fitness test performance. Movement proficiency alone does not influence physical performance in junior elite athletes.